NILAI MULTIKULTURAL BERBASIS KEARIFAN LOKAL DI PESANTREN KULON BANON - KAJEN - Rif'an, Ali (STAI Ma'had Aly Al-Hikam Malang, 2020)
Multiculturalism in pesantren Kulon Banon is a inevability by design or naturally. This study aims to produce a multicultural value inheritance construction built in the process of inheriting local wisdom values. This Ethographic research by sequence methods. Informants in this research are Kyai, asatidz, and santries by snowball sampling tecnique. Researchers were present to extract data from informants, its indept interviews and participatory observation. Data analysis used is domain analysis with technical of philosopy analysis by credibitity, transferabitity, dependability and confirmability. Validity data by persistent observation, triangulation, member check, peer reviewing; and referencial adequacy check. The results of study in local wisdom based multicultural values developed in the Pesantren Kulon Banon 6 key concept were identified: tawassut (moderate), iftitah (inclusive), tasamuh (tolerance), ukhuwwah (brotherhood), As Salam (peace) and masuliyah (responsibility). (2) The process of inheriting multicultural values based on local wisdom includes content, processes, methods and agents as elements that work in one cybernetics system, namely institutionalization, socialization, internalization and control carried out in an integrated process.